Nursing assistance in childcare consultation for child development assessment - Kominek, Andressa; Serbena, Daniel Rodrigo; Gusson de Camargo, Luiz Gustavo; Schroeder Abreu, Isabella; Mota Ferreira, Luana; Marcondes Sari, Marcel Henrique; Sartori Bonini, Juliana; Brandão Reolon, Jéssica (Disciplinarum Scientia | Saúde, 2024)
During childcare, conducting consultations for childcare plays a crucial role in identifying potential neurodevelopmental delays in infants. Objective: To explore the relevance of nursing support in assessing child development for neurological deficits during childcare consultations in literature published between 2018 and 2023. Methods: A narrative review was conducted using the databases “Biblioteca Virtual de Saúde” and “Scientific Electronic Library Online.” The keywords used were: “childcare advice,” “care,” and “infantile development”; the Boolean operators “or” and “and” were also utilized. Results: A total of 70 articles were found in the Biblioteca Virtual de Saúde and 44 in the Scientific Electronic Library Online. However, only 5 articles from the Biblioteca Virtual de Saúde and 2 from the Scientific Electronic Library Online met the inclusion and exclusion criteria, resulting in a selection of 7 articles for the study. This narrative review reveals vulnerabilities in the approach to childcare and infant development, including the absence of a comprehensive assessment of the child and various barriers that impact the quality of childcare advice. Conclusions: The findings emphasize the significance of ongoing childcare consultations involving health professionals and caregivers to adequately address the child’s needs and ensure healthy growth and development.